Solar Induced Photocatalytic Degradation of Methylene Blue by CdS/Ag2O Nanocomposites. Issue 14 (8th April 2020) - Sophia, P. Joice; Balaji, D.; James Caleb Peters, T.; Chander, D. Sathish; Vishwath Rishaban, S.; Vijaya Shanthi, P.; Nagavenkatesh, K. R.; Kumar, M. Rajesh
Abstract: Present investigation reports the synthesis of stable as well as visible‐light active CdS/Ag2 O nanocomposite photocatalysts in three varied ratios to be engaged in degradation of methylene blue (MB) dye. As‐synthesized photocatalysts have been characterized with the aid of diverse characterization techniques such as X‐ray diffraction (XRD), FT‐Raman, Fourier transform infrared spectroscopy (FT‐IR), X‐ray photoelectron spectroscopy (XPS), UV‐visible and Photoluminescence (PL) spectroscopy, and transmission electron microscopy (TEM). XRD pattern clearly depicts the presence of hexagonal CdS phase and cubic Ag2 O phase. Results show a remarkable enhancement of photocatalytic activity for MB degradation especially for CdS/Ag2 O nanocomposite with maximum efficiency up to 88.8 %. Moreover, the effective bandgap of CdS/Ag2 O (1 : 2) nanocomposite has been significantly reduced to 1.71 eV from pure CdS (2.15 eV). It can be derived that CdS/Ag2 O photocatalysis may be envisaged for treatment of diluted waste water containing organic pollutants. Abstract : High quality CdS/Ag2 O nanocomposites have been prepared by co‐precipitation method. CdS/Ag2 O nanocomposite is highly efficient in the visible light photodegradation (88.8 %) and provides a simple strategy to design photocatalyst with higher efficiency and stability.